Masalah Pelayanan Publik di Indonesia Dalam Perspektif Administrasi Publik - Abdul Mahsyar (Department of Government Studies Universitas Muhammadiyah Makassar, 2011)
Public always demanded quality public services from the bureaucrats, even though these demands are not in line with expectations because the empirically public services that occurred during this still characterized by such things asconvoluted, slow, expensive, exhausting, uncertainty. Under such circumstances occur because people are still positioned as the party to “serve” is not being served. If considered public service issues in Indonesia, the main problems of public service today is associated with improved quality of service itself. According to Albrecht and Zemke (1990) the quality of public services is the result of interaction of various aspects, the system of care, human resources service provider, strategy, and customers. While Mohammad (2003) states that quality service is dependent on aspects such as how the pattern of its implementation, support human resources, and institutional management . New Perspectives for Public Service and Good Governance is considered most appropriate for the conditions present in addressing issues of public services in Indonesia, using a model like the model citizen’s charter, model KYC (Know Your Customer), and m-Government model.Publik selalu menuntut kualitas pelayanan publik dari birokrat, meskipun tuntutan ini tidak sesuai dengan harapan karena pelayanan publik secara empiris yang terjadi selama ini masih ditandai dengan hal-hal seperti berbelit-belit, lambat, mahal, ketidakpastian melelahkan,. Dalam keadaan seperti itu terjadi karena orang masih diposisikan sebagai pihak yang